1988
DOI: 10.1073/pnas.85.19.7351
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides prevent glutamate and kainate neurotoxicity in primary neuronal cultures of neonatal rat cerebellum and cortex.

Abstract: Using a sensitive histofluorescence staining method that allows for a quantitation of neuronal death, we compared the protective effects of gangliosides (a group of naturally occurring glycosphingolipids), phencyclidine (PCP), and MK-801 (dibenzocyclohepteneimine) on glutamate-and kainate-induced neuronal death in primary cultures of cortical and cerebellar neurons prepared from neonatal rats. PCP and MK-801 block neurotoxicity induced by glutamate doses 50 times higher than the LD50 (LD50 in Mg2+ free medium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
203
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(212 citation statements)
references
References 38 publications
7
203
0
Order By: Relevance
“…Inhibition of PKC activity is protective during several models of ischemic injury, including anoxia (Maiese et al, 1993b), NO exposure (Maiese et al, 1993b,c), glutamate toxicity (Favaron et al, 1988), and animal models of global ischemia (Hara et al, 1990). In contrast to these studies, the down regulation of PKC activity with PMA (1 f..L M) and the combined application of either bFGF or EGF reduced the protective effects of the growth factors during anoxia and NO exposure.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Inhibition of PKC activity is protective during several models of ischemic injury, including anoxia (Maiese et al, 1993b), NO exposure (Maiese et al, 1993b,c), glutamate toxicity (Favaron et al, 1988), and animal models of global ischemia (Hara et al, 1990). In contrast to these studies, the down regulation of PKC activity with PMA (1 f..L M) and the combined application of either bFGF or EGF reduced the protective effects of the growth factors during anoxia and NO exposure.…”
Section: Discussionmentioning
confidence: 97%
“…15, No. 3, 1995 against glutamate tOXICIty (Favaron et al, 1988), anoxia (Maiese et al, 1993b), and NO (Maiese et al, 1993b,c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) and LPS-and IFN-γ-treated microglia (data not shown). Furthermore, several studies indicated that gangliosides increase the rates of neuritogenesis both in vivo and in vitro (Ferrari et al, 1983;Mendez-Otero and Santiago, 2003;Roisen et al, 1984) and possess a neuroprotective action (Favaron et al, 1988;Geisler et al, 1991;Karpiak et al, 1990;Manev et al, 1990;Seren et al, 1990). These effects have partly been explained by the fact that GM1 induces a rapid and significant increase in the amount of NT-3, which was observed in fibroblast cells and cerebellar granule cells (Rabin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Dissociated neurons enriched in granule cells (about 95%) were prepared from cerebella of 8-day-old Sprague-Dawley rats and cultured for 8-9 days in medium containing 25 mM K ϩ as described (18).…”
Section: Methodsmentioning
confidence: 99%